Energia dal mare: modelli numerici e GIS per la valutazione del potenziale energetico - Caiaffa, Emanela; Sannino, Gianmaria; Bargagli, A.; Carillo, A. (GEOmedia, 2012)
Attraverso l'uso di modelli numerici oceanografici applicati al Mar Mediterraneo i ricercatori del laboratoriodi modellistica climatica e impatti dell'ENEA stanno valutando il potenziale energetico contenuto nel motoondoso lungo la fascia costiera e più in generale nei mari italiani, allo scopo di identificare i siti più idoneiall'installazione di impianti di conversione del moto ondoso in energia elettrica. Energy from the sea: numerical models and GIS for the evaluation of potential production Marine renewable energy is an emerging sector with great potential to contribute in achieving European renewable energy and decarbonisation targets. Marine renewable energy is here defined to include both wave and tidal current energy. With a diverse set of technologies in development and policy support mechanisms introduced in a number of European countries, the sector is working towards achieving commercial deployments in the near future. The present paper after a short and simple description of the WAve prediction Model (WAM), a numerical wave model to assess the wave potential energy in the Mediterranean basin, describes the potential advantages in in-tegrating the numerical results in a GIS (Geographic Information System) containing environmental and territorial data. The analysis of multiple layers of geo-referenced information allows to explore the spatial relationship between the wave energy poten-tial and other variables such as the location of protected areas or navigational routes. This kind of analysis helps identifying the most suitable areas for the the installation of wave energy converters. As an example, in order to better highlight the results along the Italian coast, the values of the potential energy, extracted along the coast (about 12 km from the coast), have been included in a series of thematic maps.